SAVING RESOURCES IN THE CONSTRUCTION OF HYDROELECTRIC POWER PLANTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article describes run-of-the-river hydroelectric power plants. The authors specify the importance of performing technical and economic calculations in justifying the large-sized units of the water-supplying channel of a run-of-the-river hydroelectric power plant: turbine pits and suction (discharge) pipes. The study shows that the amount of construction work and the total cost of building a hydroelectric power plant depend on the size of these water supply units. The research objective is to analyze the validity of establishing the main dimensions of the suction pipes for modern technical and economic conditions. The researchers use the discounted income method. The calculations are performed for a hydroelectric power plant with an elbow suction pipe. The analysis of how the operating conditions of a hydroelectric power plant influence the savings of construction resources is carried out. The analysis shows that saving construction resources by reducing the length of the suction pipe is justified if the hydroelectric power plamt is designed to work only at peak power loads. For hydroelectric power plants operating at semi-peak or base power loads, the additional construction costs would be appropriate if leading to the decrease in pressure loss and to the increase in electricity generation.